2020
DOI: 10.1016/j.nicl.2020.102324
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity during evaluation of self-relevance in women with borderline personality disorder

Abstract: Highlights: Appraisal of self-relevance is disturbed in borderline personality disorder (BPD). We introduce the first neuroimaging study about self-relevance processing in BPD. Besides the CMS, the MNS and the SMA are involved in self-relevance processing. Functional connectivity of CMS is altered in BPD during self-relevance evaluations. In BPD, valence affects the functional connectivity during self-relevance ratings. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…BPD‐tb‐17 129 demonstrated that BPD patients, compared to HC, did not show a positive correlation between memory task performance and left anterior hippocampal activity. BPD‐tb‐18 130 showed decreased FC between the hippocampus and ACC during a memory task in the BPD group. The hippocampus is a well‐known structure that is responsible for consolidating short‐term, long‐term, and spatial memory.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…BPD‐tb‐17 129 demonstrated that BPD patients, compared to HC, did not show a positive correlation between memory task performance and left anterior hippocampal activity. BPD‐tb‐18 130 showed decreased FC between the hippocampus and ACC during a memory task in the BPD group. The hippocampus is a well‐known structure that is responsible for consolidating short‐term, long‐term, and spatial memory.…”
Section: Discussionmentioning
confidence: 94%
“…BPD‐tb‐17 129 and BPD‐tb‐18 130 both employed memory‐based tasks and discovered hippocampal abberancies in BPD patients. BPD‐tb‐17 129 demonstrated that BPD patients, compared to HC, did not show a positive correlation between memory task performance and left anterior hippocampal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the triple network’s FC have been widely documented in BPD [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Our results extend this evidence showing for the first time that triple network’s impairment in BPD also affects WM microstructure (i.e., SC), while the circuits’ morphology is spared.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of a triple network’s model dysfunction in BPD is supported by resting-state functional MRI studies reporting SN, DMN, and ECN functional connectivity (FC) alterations in patients compared to healthy controls (HC). Aberrant FC in the SN has been associated with emotional and social behavior dysregulations, lower metacognitive abilities, altered reward and salience processing, and impaired self-relevance evaluation [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], while in the DMN have been associated to emotional dysregulation, including pain processing [ 4 , 11 , 12 , 13 ]. Finally, FC alterations in the ECN have been associated to impulse dyscontrol [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some neuroimaging studies show resting state alterations of structural and functional connectivity, suggesting that traumatic disintegration compromises different mental functions as trait vulnerability [79][80][81]. On the other hand, several studies demonstrate that aberrant functional connectivity emerges only after an emotional task or a trauma trigger [70,74,[82][83][84].…”
Section: The Role Of Attachment Trauma In Determining Mental Disinteg...mentioning
confidence: 99%